2012
DOI: 10.1128/jb.00844-12
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence and Comparative Analysis of the Superb Aromatic-Hydrocarbon Degrader Rhodococcus sp. Strain DK17

Abstract: e Rhodococcus sp. strain DK17 is capable of utilizing various derivatives of benzene and bicyclics containing both aromatic and alicyclic moieties as sole carbon and energy sources. Here, we present the 9,107,362-bp draft genome sequence of DK17 and its genomic analysis in comparison with other members of the genus Rhodococcus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…WGM utilize singlemolecule restriction examination to acquire results concerning the magnitude of the control splinter and their substantial positions beside the DNA strand [45]. Whole genome has been exploit in a number of functions, which comprised of phylogenetic analyses and genotyping of associated with microbial isolates [46,47], discovery of outsized genomic structural rearrangements or variations [48,49], and quality control or verification for genome sequences which were assembled [50,51]. Physical genome maps based a restriction also having the potential to be used as a model for the exact arrangement of NGS contigs and to assist concluding the spaces between mapped contig.…”
Section: Whole Genome/targeted Re-sequencingmentioning
confidence: 99%
“…WGM utilize singlemolecule restriction examination to acquire results concerning the magnitude of the control splinter and their substantial positions beside the DNA strand [45]. Whole genome has been exploit in a number of functions, which comprised of phylogenetic analyses and genotyping of associated with microbial isolates [46,47], discovery of outsized genomic structural rearrangements or variations [48,49], and quality control or verification for genome sequences which were assembled [50,51]. Physical genome maps based a restriction also having the potential to be used as a model for the exact arrangement of NGS contigs and to assist concluding the spaces between mapped contig.…”
Section: Whole Genome/targeted Re-sequencingmentioning
confidence: 99%
“…A comparison between the draft genome of 311R and the 12 genomes/draft genomes of Rhodococcus sp. DK17 ( 17 ), Rhodococcus sp. JVH1 ( 18 ), R. jostii RHA1 ( 19 ), R. erythropolis PR4 ( 20 ), R. erythropolis SK121 (BioProject PRJNA55853), R. erythropolis CCM2595 ( 21 ), R. erythropolis R138 ( 22 ), R. opacus B4 ( 3 ), R. opacus PD630 ( 7 ), R. equi 103S ( 8 ), R. pyridinivorans SB3094 ( 23 ), and Rhodococcus sp.…”
Section: Genome Announcementmentioning
confidence: 99%
“…strain DK17 is also able to utilize phthalate as a growth substrate via the Gram-positive pathway [6,7]. DK17 possesses three megaplasmids (380 kb pDK1, 330 kb pDK2, and 750 kb pDK3), and the phthalate operons in DK17 are duplicated and are present on both pDK2 and pDK3 [6,8]. It was previously shown that both copies of the phthalate operon are equally functional in DK17 [9].…”
Section: Introductionmentioning
confidence: 99%